Evaluate the clinical efficacy of traditional Chinese medicine as the neoadjuvant treatment in reducing the incidence of hepatocellular carcinoma in patients with hepatitis B-related cirrhosis: a systematic review and meta-analysis - Tu, An; Zhu, Xiaoning; Dastjerdi, Paniz Zarghami; Yin, Yue; Peng, Mengyun; Zheng, Ding; Peng, Zhaoxuan; Wang, Encheng; Wang, Xiaodong; Jing, Wang (Elsevier Ltd, 2024)
Background: Traditional Chinese Medicine (TCM), has been used for hepatocellular carcinoma (HCC) at every therapeutic stage, even before tumor formation. However, the efficacy of TCM in reducing the incidence of HCC in patients with chronic hepatitis B-related cirrhosis remains unclear. This study aims to address this gap. Methods: Publications were collected from PubMed, EMBASE, Cochrane Library, Web of Science, CNKI, Sino Med, VIP, and Wan Fang Databases. Relative risk (RR) was calculated with a 95 confidence interval (CI). Heterogeneity was assessed. The Cochrane Collaboration's tool was used to assess the risk of bias. Results: 10 studies with 2702 patients showed that the combination therapy significantly reduced the incidence of HCC in patients with post-hepatitis B cirrhosis at 1, 3, and 5 years. However, the preventive effects of TCM were in compensated cirrhosis, but not the decompensated cirrhosis. Furthermore, TCM correlated with improved liver function and enhanced virological response. Conclusion: Combination therapy with TCM demonstrated the certain potential in reducing the incidence of HCC in patients with hepatitis B cirrhosis. This is attrinuted to the improvement of liver function and enhancement of the viral response. However, the efficacy of TCM in the field still needs more high-quality RCTs to provide stronger evidence in the future.